CT Scan of Nesmin from Akhmim: New Data on the Belgrade Mummy - Branislav Anđelković; Jonathan P. Elias (Etnoantropološki Problemi, 2021)
An anthropoid wooden coffin with human mummy was purchased in Luxor in February 1888 by the Serbian mécène and world traveler Pavle Riđički (1805‒1893). Due to historical, political and cultural circumstances the first studies of the mummy did not start until May 1993. The ancient ‘patient’ ‒ Nesmin, stolist-priest of Akhmim, son of Djedhor (son of Wennefer, son of Djedhor) born to Chay-Hathor-Imw/Tjay-Hathor-imw ‒ who became known as the Belgrade mummy ‒ underwent a CT scan at the University of Belgrade, Faculty of Dental Medicine, Diagnostic Radiology Center. The present paper provides the first complete analysis of the CT scan. At the time of death (350‒325 B.C.) Belgrade Nesmin was between 35 and 40 years old. A proper bioanthropological study is presented. The mummification features are discussed. The distribution of funerary amulets on the mummy has been established. The mummy’s cultural biography is specified. A museum superstition phenomenon is noted.